Intonation of questions and requests in lower intermediate adult EFL students - Vaca Barragán, Diana Alejandra (2021)
This paper investigates the intonation of questions and requests produced by 10 adult lower intermediate EFL students. The aim of this study is to identify and analyze the most common intonation mistakes. It is significant to study the current state of intonation in order to propose methodological activities to improve specific intonation problems. In fact, the study compares the pitch contours of two questions and two requests produced by native speakers with the intonation of EFL learners. This descriptive study concluded that: the learners seem not to be aware of pitch contours and the function of intonation patterns; and that the L1 influences the production of the L2. These results suggest that some technological tools such as Praat can be used in the process of teaching and learning intonation.